2002
DOI: 10.1103/physreve.66.046219
|View full text |Cite
|
Sign up to set email alerts
|

Parameter ranges for the onset of period doubling in the diode resonator

Abstract: One of the classic problems in the study of nonlinear dynamics has been the diode resonator. Previous work with the diode resonator sought to explain the causes of period doubling and chaos, and often used simplified models. This paper instead seeks to link the onset of nonlinear dynamical effects to measurable parameters by comparing experiments and numerical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The chaotic behaviour has already been observed in a microwave limiter circuit [1], in 'R-L-diode' circuits [2][3][4][5][6][7] and also in VHF microstrip oscillator [8]. The doubling period has been observed in 'line-diode' circuits in the case of partial reflection [7].…”
Section: Introductionmentioning
confidence: 93%
“…The chaotic behaviour has already been observed in a microwave limiter circuit [1], in 'R-L-diode' circuits [2][3][4][5][6][7] and also in VHF microstrip oscillator [8]. The doubling period has been observed in 'line-diode' circuits in the case of partial reflection [7].…”
Section: Introductionmentioning
confidence: 93%
“…Whether a simple circuit can produce period doubling and chaos is one of the most challenging problems in the field of chaos [1][2][3]. The driven RLD circuit is studied widely because of its typicality [4][5][6]. With further research in nonlinear systems, many types of diodes, such as ordinary diode, SiC, and PIN diode, have been put to use, but SBD has never been adopted [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that nonlinear capacitance and reverse recovery time are the main necessary conditions for producing chaos and period doubling. There have been different schools of thought debating which is the main reason, but some viewpoints consider that the two views are essentially the same [4].…”
Section: Introductionmentioning
confidence: 99%
“…The chaotic behavior has already been observed in a microwave limiter circuit [4], in 'R-L-Diode' circuits [5] and also in VHF microstrip oscillator [6]. Some theoretical approaches have been proposed for diode resonator [7,8]. In this paper, we present a theoretical study in order to understand the origin of microwave chaotic behavior in front-end RF limiter circuits.…”
Section: Introductionmentioning
confidence: 99%